Truncating ARL6IP1 variant as the genetic cause of fatal complicated hereditary spastic paraplegia - Salma M. Wakil; Safa Alhissi; Haya Al Dossari; Ayesha Alqahtani; Sherin Shibin; Brahim T. Melaiki; Josef Finsterer; Amal Al-Hashem; Saeed Bohlega; Anas M. Alazami (BMC, 2019)
Abstract Background Mutations in ARL6IP1, which encodes a tetraspan membrane protein localized to the endoplasmic reticulum (ER), have been recently described in a large family with a complicated form of hereditary spastic paraplegia (HSP). Case presentation We sought to expand the HSP phenotype associated with ARL6IP1 variants by examining a Saudi kindred with a clinically more severe presentation, which resulted in spontaneous neonatal death of both affected siblings. Clinical features encompassed not only spastic paraplegia but also developmental delay, microcephaly, cerebral atrophy, periventricular leukoencephalopathy, hypotonia, seizures, spasticity, jejunal stricture, gastrointestinal reflux, neuropathy, dysmorphism and respiratory distress. We performed clinical assessment and radiological studies of this family, in addition to homozygosity mapping and whole exome sequencing (WES) to identify the disease-associated variant. Homozygosity mapping localized the causative gene to a region on chromosome 16 harboring ARL6IP1. WES of the index case identified the homoallelic nonsense variant, c.112C > T in ARL6IP1 that segregated with the phenotype and was predicted to result in loss of the protein. Allelic expression analysis of the parents demonstrated downward pressure on the mutant allele, suggestive of nonsense-mediated decay. Conclusions Our report shows that the phenotype associated with ARL6IP1 variants may be broader and more acute than so far reported and identifies fatal HSP as the severe end of the phenotypic spectrum of ARL6IP1 variants.